The Links between Inflation Uncertainty and Investment in Iran - Akbar Komijani; Ramin Mojab (Faslnāmah-i Pizhūhish/Nāmah-i Iqtisādī, 2011)
Uncertainty results from economic and noneconomic government policies. Thispaper tries to identify the benefits or the costs of these uncertainties by analyzingthe relationship between Inflation uncertainty and Investment in Iran in quarterlyperiod of 1368:1-1387:2 (1989:1-2008:2). The results confirm a negativerelationship between inflation uncertainty and investment.